Encouraging experience using multi‐transgenic xenografts in a pig‐to‐baboon cardiac xenotransplantation model. (22nd September 2017) - Chan, Joshua L.; Singh, Avneesh K.; Corcoran, Philip C.; Thomas, Marvin L.; Lewis, Billeta GT; Ayares, David L.; Vaught, Todd; Horvath, Keith A.; Mohiuddin, Muhammad M.
Abstract: Background: Innovations in transgenic technology have facilitated improved xenograft survival. Additional gene expression appears to be necessary to overcome the remaining immune and biologic incompatibilities. We report for the first time the novel use of six‐gene modifications within a pig‐to‐baboon cardiac xenotransplantation model. Methods: Baboons (8‐15 kg) underwent heterotopic cardiac transplantation using xenografts obtained from genetically engineered pigs. Along with previously described modifications (GTKO, hCD46), additional expression of human transgenes for thromboregulation (endothelial protein C receptor, tissue factor pathway inhibitor, thrombomodulin), complement inhibition (decay accelerating factor), and cellular immune suppression (hCD39, hCD47) was used. Immunosuppression consisted of targeted T‐cell and B‐cell depletion and conventional anti‐rejection agents. Results: Heterotopic cardiac transplantations were performed without complication. Flow cytometry and immunohistochemistry on donor biopsies confirmed transgenic phenotype. In contrast to the prior three‐gene generation, significant coagulopathy or consumptive thrombocytopenia has not been observed in the six‐gene cohort. As a result, these recipients have experienced decreased bleeding‐related complications. Pro‐inflammatory responses also appear to be mitigated based on cytokine analysis. Baboons survived the critical 30‐day post‐operative period when mortality has historically been highest, with no evidence of graft rejection. Conclusions: The inclusion of additional human genes in genetically engineered pigs appears to confer superior xenograft outcomes. Introduction of these genes has not been associated with adverse outcomes. This multifactorial approach to genetic engineering furthers the prospect of long‐term cardiac xenograft survival and subsequent clinical application.